Floods in a changing climate - Teegavarapu, Ramesh S. V., 1970- (International hydrology series, 2012)
"Measurement, analysis and modeling of extreme precipitation events linked to floods is vital in understanding the world's changing climate. This book examines and documents the impacts of climate change and climate variability on extreme precipitation events, providing methods for assessment of the trends in these events, and their impacts. It also provides a basis to develop procedures and guidelines for climate-adaptive hydrologic engineering. Topics covered include approaches for assessment of hydrometerological floods, recent developments in hydrologic design for flood mitigation, and applications and limitations of improved precipitation forecasts, using information about internal modes of climate (teleconnections). State-of-the-art methodologies for precipitation analysis, estimation and interpolation are included, and exercises for each chapter, supported by modelling software and computational tools available online at www.cambridge.org/teegavarapu, enable the reader to apply and engage with the innovative methods of assessment"--